2009
DOI: 10.1088/0952-4746/29/2/n02
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the dose received by students and staff in schools in the Rawalpindi region of Pakistan due to indoor radon

Abstract: Studies concerning measurements of indoor radon levels were carried out in 60 schools in the Rawalpindi region of Pakistan. In each school, six CR-39 based NRPB type radon detectors were installed and exposed to the indoor radon in two cycles (each of six months' duration). After exposure, the detectors were removed, etched in 6 M NaOH for 16 h at 80 degrees C, and the tracks were counted under an optical microscope. The measured track densities were then related to radon concentrations, from which the radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
2
5
1
Order By: Relevance
“…In this study, the average radon concentration in the two 6‐month exposure periods appears (on average) to be nearly equivalent (although the variation for single schools is considerable), similar to the results of the two studies carried out in Pakistan (Rahman and Matiullah Anwar, ; Rahman et al., ), whereas two other studies carried out in Japan (Oikawa et al., ) and in an Italian province (Trevisi et al., ) report higher radon concentrations in winter than in summer. Our results may be related to the specific usage patterns of the schools, which are kept closed during summer vacation (2.5 months), allowing the radon concentration to build up inside.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, the average radon concentration in the two 6‐month exposure periods appears (on average) to be nearly equivalent (although the variation for single schools is considerable), similar to the results of the two studies carried out in Pakistan (Rahman and Matiullah Anwar, ; Rahman et al., ), whereas two other studies carried out in Japan (Oikawa et al., ) and in an Italian province (Trevisi et al., ) report higher radon concentrations in winter than in summer. Our results may be related to the specific usage patterns of the schools, which are kept closed during summer vacation (2.5 months), allowing the radon concentration to build up inside.…”
Section: Discussionsupporting
confidence: 86%
“…Since the number of sampling points on lower floors (ground floor and basement) was much higher compared with those on the first floor, radon values relating to each building can be considered as being rather overestimated. Nevertheless, it can be pointed out that e as in other radon measurement campaigns in schools (Clouvas et al, 2011;Rahman et al, 2009;Synnot et al, 2006) e the choice of monitoring principally rooms located on the ground floor arose from the fact that, except for secondary schools, a large number of schools are ground-floor-only structures.…”
Section: Overview Of Main Resultsmentioning
confidence: 99%
“…Considering the latter and as far as the authors’ knowledge goes, in the last five years 19 studies regarding radon in indoor air of nursery and primary schools can be found. The majority of them were only focused on primary schools [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], while others also considered nursery schools [ 10 , 22 , 23 , 24 , 25 , 26 ] and some others only considered nursery schools [ 27 , 28 ]. The extent of the studies varied considerably from study to study.…”
Section: Introductionmentioning
confidence: 99%